Confecção de modelo canino 3D para ensino em anestesiologia veterinária - Lobo, Paloma Moraes (2023)
Epidural block in dogs is a locoregional anesthesia technique widely used in veterinary medicine, becoming a valuable tool in the anesthetic protocol to provide more effective analgesia to patients. For this, professionals must follow strict guidelines and have technical skills. In this context, the development of practical clinical skills is vital for veterinary education, but traditional teaching methods have been insufficient to ensure a consistent level of competence in recent graduates. The introduction of non-animal alternatives for educational purposes has contributed to the development of simulation-based teaching, an innovative and accessible field of study capable of improving students' practical skills and reducing the use of live animals and cadavers. Despite its use in several areas of veterinary education, so far there are no conclusive results regarding the development of accessible simulators capable of effectively improving the teaching of practical skills in epidural block training in dogs. Therefore, this article represents a pioneering study that aims to share an innovative method for making a realistic simulator for epidural block training in dogs. The simulator was fully developed by veterinary researchers with limited experience in the area of 3D printing, and after preliminary analysis, it showed good performance and an excellent ultrasound anatomy. Future work will focus on the formal validation of this simulator in order to improve the preclinical proficiency of students and residents in veterinary anesthesiology.